Occurrence probability and amplitude of equatorial ionospheric irregularities associated with plasma bubbles during low and moderate solar activities (2008–2012). Issue 2 (7th February 2014) - Huang, Chao‐Song; de, O.; Roddy, P. A.; Hunton, D. E.; Liu, J. Y.; Chen, S. P.
Abstract We present a statistical analysis of the occurrence probability of equatorial spread F irregularities measured by the Communication/Navigation Outage Forecasting System satellite during 2008–2012. We use different criteria (plasma density perturbations, ΔN, and relative density perturbations, ∆N/N0) to identify the occurrence of ionospheric irregularities. The purpose of this study is to determine whether the occurrence probability of irregularities is the same for different criteria, whether the patterns of irregularity occurrence vary with solar activity and with local time, and how the patterns of irregularity occurrence are correlated with ionospheric scintillation. It is found that the occurrence probability of irregularities and its variation with local time are significantly different when different identification criteria are used. The occurrence probability based on plasma density perturbations is high in the evening sector and becomes much lower after midnight. In contrast, the occurrence probability based on relative density perturbations is low in the evening sector but becomes very high after midnight in the June solstice. We have also compared the occurrence of ionospheric irregularities with scintillation. The occurrence pattern of the S4 index and its variation with local time are in good agreement with the irregularity occurrence based on plasma density perturbations but are significantly different from those based on relative density perturbations. This study reveals that the occurrence pattern of equatorial ionospheric irregularities varies with local time and that only the occurrence probability of irregularities based on plasma density perturbations is consistent with the occurrence of scintillation at all local times.